2022
DOI: 10.3892/etm.2022.11328
|View full text |Cite
|
Sign up to set email alerts
|

Bisdemethoxycurcumin attenuates OVA‑induced food allergy by inhibiting the MAPK and NF‑κB signaling pathways

Abstract: Bisdemethoxycurcumin (BDMC) is an important ingredient derived from turmeric in addition to curcumin. It has been reported that BDMC can be used to treat mast cell-mediated allergic diseases. In the present study, a food allergy (FA) murine model sensitized by intraperitoneal injection followed by oral challenge with ovalbumin (OVA) was established. BDMC was orally administered at 100 and 200 mg/kg for 11 days in the challenge phase to treat OVA-induced FA mice. FA symptoms such as diarrhea score, anaphylactic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Due to the lack of IgG4 isotype ( 59 61 ), only total and OVA-specific IgG1 can be detected in the FA mice model. Elevated OVA-sIgG1 has been observed in FA mice model ( 54 , 62 , 63 ). We observed a similar reduction of OVA-sIgE and sIgG1 after IF when compared to a free diet.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the lack of IgG4 isotype ( 59 61 ), only total and OVA-specific IgG1 can be detected in the FA mice model. Elevated OVA-sIgG1 has been observed in FA mice model ( 54 , 62 , 63 ). We observed a similar reduction of OVA-sIgE and sIgG1 after IF when compared to a free diet.…”
Section: Discussionmentioning
confidence: 99%
“…Our data agrees with those of Kim and collaborators [44], who showed that cinnamaldehyde produced anti-inflammatory effects in RAW 264.7 murine macrophages by inhibiting ERK, JNK and p38 MAPKs phosphorylation. Moreover, bisdemethoxycurcumin was reported to diminish the inflammatory status in a food allergy murine model sensitized after oral challenge with ovalbumin via the inhibition of MAPKs phosphorylation [45].…”
Section: Discussionmentioning
confidence: 99%
“…These effects were accompanied by inhibition of the MAPK signaling pathway and the nuclear translocation of NF-κB. This mechanism may be responsible for the reduced anaphylaxis symptoms, lower diarrhea scores, and attenuated increase in rectal temperature in mice after OVA stimulation [92].…”
Section: Spices 281 Curcuminmentioning
confidence: 91%
“…The oral administration of curcumin reduced serum histamine, PGD 2 , and LTC 4 (≈50%) levels in a mouse model of passive systematic anaphylaxis [71]. Curcumin showed a greater effect on histamine (≈70%) and OVA-specific IgE (≈80%) reduction compared to BDMC, demonstrating a less than 50% reduction in both parameters in OVA-stimulated BALB/c mice [72,92,93]. Curcumin treatment in a mouse model of allergic rhinitis reduced TNF-α cytokine levels by about 70% by suppressing the phosphorylation of the Src kinases Fyn, Lyn, and Syk [72].…”
Section: Spices 281 Curcuminmentioning
confidence: 97%